Becoming Black : Creating Identity in the African Diaspora - Wright, Michelle M., 1968- (Book collections on Project MUSE., 2004)
A theoretical troubling of the assumptions of uniformity in Blackness, comparing writings by and about African diasporic subjects from the U.S., Britain, France, and Germany.